Outward Bound and outdoor adventure education - Mateer, Timothy J. (Annales kinesiologiae (Koper), 2022)
Outdoor adventure education (OAE) programming is often referenced as an ef-fective intervention that encourages a wide array of outcomes in participants such as increased confidence, independence, and communication skills. However, as outdoor adventure education continues to increase globally, what does the academic literature say about the outcomes related to these programs? Hattie, Marsh, Neill, and Richards (1997) conducted the last major review of program efficacy in this realm. This updated scoping review, largely following PRISMA guidelines (Tricco et al., 2018), aims to summarize the academic literature on one of the primary outdoor adventure education providers internationally, Outward Bound (OB). Fifty-four studies, published betwe-en 1995 and 2019, have been summarized in this review. Utilizing Outward Bound International’s (OBI) framework of “people”, “place”, and “process”, themes and gaps in the literature are explored. Specifically, the OB literature has progressed since 1995 in demonstrating social and emotional outcomes in a variety of settings, a better understanding of the nature of effective programming, and further documenting the role the instructor plays in the learning experience. Recommendations are provided on developing more rigorous methodologies for future research, understanding the role of the physical environment in the learning experience, and utilizing theoretical approa-ches to integrate outdoor adventure education into broader academic realms
Keywords: adventure education; čustveno učenje; emotional learning; experiental learning; izkustveno učenje; izobraževanje na prostem; izobraževanje skozi pustolovščine; outdoor education; Outward Bound; pregledne študije; scoping review